Flagging Facebook Falsehoods: Self-Identified Humor Warnings Outperform Fact Checker and Peer Warnings. Issue 5 (3rd October 2019) - Garrett, R Kelly; Poulsen, Shannon
Abstract: We present two studies evaluating the effectiveness of flagging inaccurate political posts on social media. In Study 1, we tested fact-checker flags, peer-generated flags, and a flag indicating that the publisher self-identified as a source of humor. We predicted that all would be effective, that their effectiveness would depend on prior beliefs, and that the self-identified humor flag would work best. Conducting a 2-wave online experiment ( N = 218), we found that self-identified humor flags were most effective, reducing beliefs and sharing intentions, especially among those predisposed to believe the post. We found no evidence that warnings from fact checkers or peers were beneficial. Compared to the alternatives, participants exposed to self-identified humor flags exhibited less reactance to and had more positive appraisals of the flagging system. The second study ( N = 610) replicated the findings of the first and provides a preliminary test of what makes this flag work.